Praktik Penimbangan dalam Akad Jual Beli Buah Kelapa Sawit Menurut Perspektif Ekonomi Islam di Desa Sipagabu Kecamatan Aek Nabara Barumun - Akhir Saleh Pulungan,; Amhar Maulana Harahap,; Aminah Lubis,; Sakinah Tiroyan, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to determine the form of practice of weighing the sale and purchase of oil palm fruit in Sipagabu and Islamic economic review of the practice of weighing the sale and purchase of oil palm fruit in Sipagabu. The research conducted by the author is a field research that is directly related to the object under study. The method used in this research is descriptive qualitative method. Descriptive research is research that guides researchers to explore and portray social situations thoroughly, broadly and in depth. The research subjects include sellers and buyers of oil palm fruit, while the object of research is the practice of weighing in the sale and purchase contract of oil palm fruit from an Islamic economic perspective. Data collection was conducted through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion drawing. Based on the results of the research and discussion in this study, it can be concluded that the practice of buying and selling oil palm in Sipagabu Village has followed the pillars and conditions in buying and selling, even though there are deductions in each weighing of 10 kilograms and scales that shake slightly upwards, this is already a good thing.